2006
DOI: 10.1111/j.1551-2916.2006.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Flow as the Driving Force for the Densification of Low‐Temperature Co‐Fired Ceramics

Abstract: Filled glass–ceramic composites, like low‐temperature co‐fired ceramics (LTCC), must densify at temperatures <900°C. The densification mechanism of LTCC is often described by liquid‐phase sintering. The results of this paper clearly show that densification of ceramic‐filled glass–composites with a glass content above 60 wt% can be attributed to viscous sintering, which is decisively controlled by the viscosity of the glass during the heat treatment. This is demonstrated by the experimental determination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 16 publications
1
56
0
3
Order By: Relevance
“…It was found that the glass does wet the filler material is very important by investigation of the wetting behavior of the glass on the ceramic filler, and of the micro structural development [13] .…”
Section: Mechanismmentioning
confidence: 99%
“…It was found that the glass does wet the filler material is very important by investigation of the wetting behavior of the glass on the ceramic filler, and of the micro structural development [13] .…”
Section: Mechanismmentioning
confidence: 99%
“…Debido a que la sinterización es impulsada por las energías interfaciales de los poros y de los cristales dispersos en el fundido viscoso y que este proceso se desarrolla mediante un transporte de materia por flujo viscoso, a este mecanismo de sinterización también se le denomina "sinterización viscosa", incluso aún cuando no se produzca un buen mojado de las partículas rígidas por el vidrio [2]. La Figura 2.2 ilustra esquemáticamente los fenómenos clave de la sinterización viscosa de GMCs.…”
Section: Las Piezas De Vidrios Sinterizados (Sg) Y Vitrocerámicos Sinunclassified
“…= tensión superficial del vidrio; η= viscosidad del vidrio; c=8 (2) 0,5 /3π; aS y LS = radio y longitud del cilindro del modelo Scherer; n*= concentración numérica de poros; rp = radio del poro y el subíndice "0" indica el inicio de sinterización.…”
Section: Vidriosunclassified
“…It is, moreover, considered that the non-reactive liquid phase sintering (NPLS) occurred in this system [17,18]. The NLPS is one of the liquid-assisted sintering (LAS) [19]; LAS distinguishes between the NLPS, where a glass phase content of at least 20-40 vol.% is necessary for the densification and a reactive liquid phase sintering, where a glass content <20 vol.% is sufficient. The densification in the NLPS was proposed in three stages; the first stage is glass redistribution and local grain rearrangement where only slight densification occurs, the second is the main densification process including global rearrangement, glass redistribution, and closure of pores where the density from 65 to 90% of the theoretical density is accomplished, and the third is viscous flow where the residual porosity of about 10% is closed.…”
Section: Zbs Glass-doped Bi(nb 07 Ta 03 )O 4 Ceramicsmentioning
confidence: 99%